2007
DOI: 10.1080/09674845.2007.11732782
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the antioxidant defence in different developmental stages of Schistosoma mansoni by praziquantel and artemether

Abstract: Human schistosomiasis is a chronic and debilitating parasitic disease caused by parasitic trematode worms (schistosomes). Praziquantel (PZQ) is the drug of choice as it is active against all Schistosoma species, can be administered easily, has high cure and egg reduction rates, with no or only mild side effects. Rapid re-infection following treatment and the concerns about PZQ resistance has led to the search for new drugs to treat schistosomiasis. Significant progress has been made with artemisinin derivative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 20 publications
(25 reference statements)
1
9
0
Order By: Relevance
“…These results suggest that treatment with PZQ may result in a molecular response similar to that observed when schistosomes undergo oxidative stress [20]. It should be noted, however, that this conclusion is in contrast to that of El-Bassiouni et al [35] who observed that treatment of 3 or 6-week p.i. S. mansoni with up to 100 ng/mL PZQ in vitro for 1 or 3 h had no effect on the activities of superoxide dismutase, glutathione peroxidase or glutathione transferase though this may be due to the relatively low levels of PZQ employed.…”
Section: Resultsmentioning
confidence: 94%
“…These results suggest that treatment with PZQ may result in a molecular response similar to that observed when schistosomes undergo oxidative stress [20]. It should be noted, however, that this conclusion is in contrast to that of El-Bassiouni et al [35] who observed that treatment of 3 or 6-week p.i. S. mansoni with up to 100 ng/mL PZQ in vitro for 1 or 3 h had no effect on the activities of superoxide dismutase, glutathione peroxidase or glutathione transferase though this may be due to the relatively low levels of PZQ employed.…”
Section: Resultsmentioning
confidence: 94%
“…The quantitative contribution of oxidative stress to the potency of the endoperoxides remains to be established. However, the generation of ROS by ART derivatives in a variety of eukaryotic cell types [27, 28, 67], in juvenile schistosomes [68], and in P. falciparum , is clearly associated with cytotoxicity. Overall, this study provides evidence that the interaction of endoperoxides with neutral lipids may be an important component in their mechanism of action against malaria parasites.…”
Section: Discussionmentioning
confidence: 99%
“…Differently from CT-SOD, SP-SOD and GPx, the GST are not present either in the digestive tract or on the tegumentum of adult worms (Holy et al 1989). Studies aimed to evaluate the possible toxicity of the drug artemether on S. mansoni have shown that in the immature stage of the parasite (inside the intermediate host represented by the gasteropode), a depletion of parasitic GST can be observed, occurring in a time-and dose-dependent way, suggesting a possible use of this drug as schistosomicide (El-Bassiouni et al 2007). …”
Section: S Mansonimentioning
confidence: 99%